2009
DOI: 10.1037/a0014989
|View full text |Cite
|
Sign up to set email alerts
|

Associations among religiousness, social attitudes, and prejudice in a national random sample of American adults.

Abstract: Psychologists have devoted considerable theoretical and empirical attention to the scientific study of social attitudes and prejudice. Most of these studies were conducted with relatively small, nonrepresentative samples of college students. In this study, the authors analyzed self-report data from a random probability sample with over 1500 American adults. Participants answered questions about their religiousness, right-wing authoritarianism (RWA), political ideology, demographic characteristics, and attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
170
1
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(192 citation statements)
references
References 44 publications
12
170
1
9
Order By: Relevance
“…Consistently, scholarship indicates that women, higher educated people, non-religious individuals, younger generations, and political liberals are more likely to support pro-LGB policies than men, lower educated people, religious individuals, older generations, and political conservatives (Brumbaugh et al 2008;Haider-Markel and Joslyn 2008;Lewis 2011;Lewis and Gossett 2008;Olson et al 2006;Pearl and Galupo 2007;Pew Research 2013a, 2013b, 2014aRowatt et al 2009;Sherkat et al 2010;Whitehead 2010;Swank et al 2013;Woodford et al 2012). Particularly relevant to the current analyses, scholars have also pointed to regional differences to explain variation in support of pro-LGB policies.…”
Section: Literature Review Public Opinion Of Pro-lgb Policiesmentioning
confidence: 65%
See 1 more Smart Citation
“…Consistently, scholarship indicates that women, higher educated people, non-religious individuals, younger generations, and political liberals are more likely to support pro-LGB policies than men, lower educated people, religious individuals, older generations, and political conservatives (Brumbaugh et al 2008;Haider-Markel and Joslyn 2008;Lewis 2011;Lewis and Gossett 2008;Olson et al 2006;Pearl and Galupo 2007;Pew Research 2013a, 2013b, 2014aRowatt et al 2009;Sherkat et al 2010;Whitehead 2010;Swank et al 2013;Woodford et al 2012). Particularly relevant to the current analyses, scholars have also pointed to regional differences to explain variation in support of pro-LGB policies.…”
Section: Literature Review Public Opinion Of Pro-lgb Policiesmentioning
confidence: 65%
“…Yet such support and acceptance is higher among certain segments of the population than others (Hopkins et al 2013;Moore and Stambolis-Ruhstorfer 2013;Seidman 2002). Studies show that younger people, women, non-religious, and those who know an LGB person support pro-LGB policies at higher levels than other groups (Brumbaugh et al 2008;Haider-Markel and Joslyn 2008;Lewis 2011;Lewis and Gossett 2008;Olson et al 2006;Pearl and Galupo 2007;Rowatt et al 2009;Sherkat et al 2010;Swank et al 2013;Whitehead 2010;Woodford et al 2012).…”
mentioning
confidence: 99%
“…Among college studies, only the etiology of same-sex sexuality has been explored (Raiz 2006;Swank and Raiz 2010). Results suggest that those with liberal political views tend to support same-sex marriage more so than their conservative counterparts Haider-Markel and Joslyn 2008;Olson et al 2006;Rowatt et al 2009;Sherkat et al 2010;Whitehead 2010). …”
Section: Opinions About Same-sex Marriagementioning
confidence: 99%
“…Studies conducted with members of the general public have also found religion to be influential. For example, studies have found that Christian respondents, specifically evangelical and conservative Protestant Christians tend to have significantly lower levels of support for same-sex marriage than non-Christians (HaiderMarkel and Joslyn 2008;Olson et al 2006;Rowatt et al 2009;Sherkat et al 2010;Whitehead 2010). Similarly, those who consider religion to be important in their lives tend to hold less affirming opinions of same-sex marriage (HaiderMarkel and Joslyn 2005;Pearl and Galupo 2007).…”
Section: Opinions About Same-sex Marriagementioning
confidence: 99%
“…Over the past 20 years, several studies have addressed the adage "love the sinner and hate the sin" (e.g., Bassett et al, 2002;Batson, Floyd, Meyer & Winner, 1999;Fulton, Maynard & Gorsuch, 1999;Mak & Tsang, 2008;Rowatt, LaBouff, Johnson, Froese & Tsang, 2009;Veenvliet, 2008). Most of the research has evaluated the degree to which certain religious people, Christians in particular, might be able to do it -maintain positive sentiment for someone who is associated with a behavior that is considered negative, inappropriate, and morally wrong.…”
Section: Introductionmentioning
confidence: 99%